Uji Kesesuaian CT Number In Water Pada Pesawat CT Scan Merk Philip Di Instalasi Radiologi RSU BMC Padang - Nansih, Livia Ade; Artitin, Cicilia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2023)
CT number is the value of the X-ray attenuation coefficient determined by the average energy of X-rays and the absorber atomic number is expressed by the attenuation coefficient. The role of the CT number on a CT scan machine to assess and differentiate abnormalities in human organs. Compliance tests are carried out to ensure that the CT-Scan aircraft meets radiation safety requirements and provides precise and accurate diagnostic information. This research is a quantitative research with an experimental approach, carried out at the Radiology Installation of RSU Bunda Padang in June 2022 for 5 days. The population of all CT number tests, samples at five measurement points with ROI in the center of the image, at 12 o'clock, 3 o'clock, 6 o'clock and 9 o'clock directions. Research data was taken by observing, experimenting and documenting. Data analysis was compared with PERKA BAPETEN Number 9 of 2011 concerning the quality assurance of QA and QC of CT Scan aircraft.